2018
DOI: 10.1055/s-0038-1651522
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Patients with Squamous Cell Carcinoma of the Temporal Bone after Concomitant Chemoradiotherapy

Abstract: This article aims to clarify the long-term outcomes of patients with squamous cell carcinoma of the temporal bone who underwent concomitant chemoradiotherapy (CCRT). The study design was a retrospective chart review. From December 2001 to June 2014, 23 patients with cancer of the temporal bone who were treated by CCRT at the Tohoku University Hospital and the Iwate Medical University Hospital were enrolled in this study. For advanced cancer of the temporal bone, a modified docetaxel, cisplatin, and 5-fluoroura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…For locally advanced disease (T3/4), a multimodal approach involving surgery followed by adjuvant radiotherapy and chemotherapy is the mainstay of treatment. Emerging evidence suggests that concurrent chemoradiotherapy may achieve outcomes comparable to those of surgery combined with adjuvant radiotherapy 13,14 . In a meta-analysis conducted by Krystelle et al 9 , no significant difference was observed in the 5-year survival rates between patients with T1/T2 TBSCC who underwent radical surgical resection and those who received radiotherapy alone (100% vs. 81.3%, P = 0.103).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For locally advanced disease (T3/4), a multimodal approach involving surgery followed by adjuvant radiotherapy and chemotherapy is the mainstay of treatment. Emerging evidence suggests that concurrent chemoradiotherapy may achieve outcomes comparable to those of surgery combined with adjuvant radiotherapy 13,14 . In a meta-analysis conducted by Krystelle et al 9 , no significant difference was observed in the 5-year survival rates between patients with T1/T2 TBSCC who underwent radical surgical resection and those who received radiotherapy alone (100% vs. 81.3%, P = 0.103).…”
Section: Discussionmentioning
confidence: 99%
“…For locally advanced disease (T3/4), a multimodal approach involving surgery followed by adjuvant radiotherapy and chemotherapy is the mainstay of treatment. Emerging evidence suggests that concurrent chemoradiotherapy may achieve outcomes comparable to those of surgery combined with adjuvant radiotherapy 13,14 . In a meta‐analysis conducted by Krystelle et al 9 ,.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, radical RT alone has been reported to be insufficient for any stage of EAC SCC, which led to advocacy for primary treatment with surgery 16,17 . More recently in comparison with the standard of care (surgery with adjuvant RT), definitive CRT has been demonstrated in T3‐T4 tumors to yield equivalent OS rates 18–21 . However, due to lack of quality evidence from prospective randomized trials, guidelines on treatment options are not standardized.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 More recently in comparison with the standard of care (surgery with adjuvant RT), definitive CRT has been demonstrated in T3-T4 tumors to yield equivalent OS rates. [18][19][20][21] However, due to lack of quality evidence from prospective randomized trials, guidelines on treatment options are not standardized.…”
Section: Introductionmentioning
confidence: 99%